Expression of Tolerance in the Religious-Multicultural Society of Jayapura, Siak Regency - Hariyanti, Hariyanti (Jurnal Studi Agama dan Masyarakat, 2024)
This article is motivated by the harmony in diversity that exists in the multicultural society of Jayapura, Siak Regency. This research aimed to analyze expressions of tolerance in the religious-multicultural society of Jayapura, Siak Regency. The research used a descriptive qualitative design, carried out in Jayapura village, Siak district, from December 2022 to November 2023. The informants were several community figures, religious leaders, and youth leaders. Data was collected through interviews and documentation studies. The data analysis technique used the Miles and Huberman model, which consists of data collection, verification and reduction, and concluding. The research found that the people of Jayapura village come from various ethnicities, namely Javanese, Minang, Batak, and Malay as well as a variety of religions, some are Muslim and Christian, because Jayapura village has been a transmigrant area since the New Order era. However, tolerance is strongly felt in community life, such as during the celebration of religious holidays, feasts, and funerals. If there is conflict in society due to differences in views, community leaders and religious leaders in their respective communities take an important role in reconciling. This is an implementation of the values of Pancasila as the nation's way of life.